The Role of Teacher Immediacy and Teacher-Student Rapport in Shaping Academic Motivation: Evidence from Prospective Teachers in Pakistan - Hussain, Tariq; Batool, Tooba; Naz, Anjum (Journal of Development and Social Sciences, 2024)
This study aimed to examine the relationship between teacher immediacy (TI), teacher-student rapport (TSR), and academic motivation (AM) among prospective teachers in Lahore, Pakistan, while exploring gender differences. Teacher immediacy and rapport significantly impact academic motivation, aligning with social cognitive and self-determination theories. Understanding these relationships can enhance teacher education programs. A quantitative correlation research design was employed. Using multistage sampling, 455 participants from five universities were selected. Data were collected via three validated instruments: the Immediacy Behavior Scale (IBS), Teacher-Student Rapport Scale (TSRS), and Academic Motivation Scale (AMS), with reliability coefficients of 0.85, 0.75, and 0.75, respectively. Significant positive correlations were observed among TI, TSR, and AM. Male prospective teachers reported higher perceived TI and TSR, highlighting gender differences in these variables. To address gender disparities and enhance AM, teacher training programs should incorporate rapport-building and immediacy strategies, alongside gender-sensitive approaches, to foster positive teacher-student interactions.